ANALISIS MANAJEMEN SYARIAH PERAN APLIKASI MOBILE JAMINAN KESEHATAN NASIONAL (JKN) DALAM MENINGKATKAN KUALITAS PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN (BPJS KESEHATAN) KANTOR CABANG KOTA BOGOR - Saddam Hussein; Hasbi Ash Shiddieqy; Mohamad Kharis Mubarok (SAHID BUSINESS JOURNAL, 2022)
The Health Social Security Administration Agency (BPJS Kesehatan) as the organizer of national health insurance for all Indonesian people, especially for Civil Servants, TNI/POLRI, Veterans and ordinary people, seeks to improve services to all BPJS Health participants. BPJS Health provides innovation in the development of the Mobile JKN application which is useful for facilitating the services of BPJS Health participants. The purpose of this research is to find out and analyze sharia management of the Mobile JKN application, the factors of strengths and weaknesses and whether it has been able to improve services by using the Mobile JKN application at the Health BPJS Bogor City Branch Office. This research is qualitative in nature and the data collection method is by conducting interviews, observation and documentation. This data collection method was carried out on respondents, namely the Head of the BPJS Health Membership Section, BPJS Health service staff and BPJS Health participants at the Bogor City Branch office. The analysis used in this study is descriptive qualitative and to strengthen and complement the research results the authors add the data provided by the Health BPJS. The results of the study show that the Mobile JKN application has improved the quality of BPJS Health services at the Bogor City Branch Office, in addition to that BPJS Health has provided services that are accepted and benefited by participants. This is in accordance with sharia management which manages the organization to obtain optimal results and obtain blessings from Allah Subhanahu Wa Ta'ala.